Exosomal Non-Coding RNAs: Regulatory and Therapeutic Target of Hepatocellular Carcinoma - Xia, Haoming; Huang, Ziyue; Liu, Shuqiang; Zhao, Xudong; He, Risheng; Wang, Zhongrui; Shi, Wenguang; Chen, Wangming; Li, Zhizhou; Yu, Liang; Huang, Peng; Kang, Pengcheng; et al. (Frontiers in Oncology, 2021)
Exosomes are small extracellular vesicles secreted by most somatic cells, which can carry a variety of biologically active substances to participate in intercellular communication and regulate the pathophysiological process of recipient cells. Recent studies have confirmed that non-coding RNAs (ncRNAs) carried by tumor cell/non-tumor cell-derived exosomes have the function of regulating the cancerous derivation of target cells and remodeling the tumor microenvironment (TME). In addition, due to the unique low immunogenicity and high stability, exosomes can be used as natural vehicles for the delivery of therapeutic ncRNAs in vivo. This article aims to review the potential regulatory mechanism and the therapeutic value of exosomal ncRNAs in hepatocellular carcinoma (HCC), in order to provide promising targets for early diagnosis and precise therapy of HCC.